申請專利範圍之手段功能用語解釋及其侵害判斷 Interpretation and Infringement Analysis of Means Plus Function Claimed Elements - 陳佳麟 Jia-Lin Chen (Kējì Fǎxué Pínglùn, 2005)
2004 年7 月1 日修正施行的台灣專利法施行細則第18 條第8 項允許專利權人無須於申請專利範圍（claim）詳細描述技術特徵的具體結構、材料或動作，僅須敘述其所欲實施之功能，並在說明書揭露實施所述之同一功能（identical function）的相對應結構、材料或動作，其權利範圍則包含該結構、材料或動作，及其均等物。此種申請專利範圍技術特徵即所謂的「手段功能」或「步驟功能」技術特徵。美國是第一個將手段（步驟）功能技術特徵（means-plus-function element）之用語規定於專利法中的國家，其實務運作已超過半世紀，並累積了相當多的判決，而台灣專利法施行細則此規定即是參照美國專利法的相關規定。台灣智慧財產局已經有核准以此種方法撰寫申請專利範圍之專利，但目前尚未有此種申請專利範圍之權利範圍應如何解釋與判斷侵害之判決。本文整理與分析美國近年來與手段功能技術特徵有關之專利糾紛案例，藉以歸納出手段功能技術特徵之字義範圍解釋與侵害判斷之準則及應注意事項，並比較法規上對手段功能技術特徵所規定之均等物與判決上所創設出來之均等論所能主張之均等物的異同。 The Paragraph 8 of Article 18 of the amended Implementing Regulations of Taiwan Patent Law, effective on July 1, 2004, introduces a new claim-drafting rule, which allows patentees to describe a claim by the function of claimed element without the recital of structure, material, or acts in support thereof. Such kind of the claimed element, which is the so-called “means plus function element” or “step plus function element”, is construed to cover the corresponding structure, material, or acts disclosed in the specification and equivalents thereof. United States is the first country that enacted the means plus function provision in the patent law and has operated this system for more than fifty years with numerous cases being decided. The means plus function provision in the Implementing Regulations of Taiwan Patent Law is added by reference to U.S. Patent Law. Taiwan Intellectual Property Office has issued patents having claims with means plus function elements, however, courts in Taiwan have not decided cases regarding how to construe and justify infringement for such kinds of claims. This paper analyzes the recent patent infringement cases in United States that are relevant to means plus function claims, to obtain the guidelines for determining and interpreting means plus function elements as well as for justifying infringement. The differences between the literal equivalents included in means plus-function claims and equivalents under doctrine of equivalents are also compared and discussed.